2006
DOI: 10.1177/002029400603900401
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Wideband Positioning for Intelligent Security Systems

Abstract: his paper details the use of UWB positioning as a means to track the movements of individuals in real time. The work outlined here uses techniques to extract, analyse and classify positional data as part of an intelligent system designed to show the interactions between individuals and their environment. It is envisaged that such an application would be used in large public infrastructures such as an airport. Advancements in UWB technology allow for the accurate and reliable positioning of a RFID tag within an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The simulated technique could then be verified by testing subjects fitted with wireless accelerometers attached to wrists, ankles or hips. Previous studies have suggested monitoring people in public spaces by fitting them with an Ultra wideband (UWB) radio sensor, for example, as an electronic biometric identification and location ticket at an airport, [12]. UWB positioning is an emerging technology with many potential benefits for security.…”
Section: Planned Work With the Gait Analysis Laboratorymentioning
confidence: 99%
“…The simulated technique could then be verified by testing subjects fitted with wireless accelerometers attached to wrists, ankles or hips. Previous studies have suggested monitoring people in public spaces by fitting them with an Ultra wideband (UWB) radio sensor, for example, as an electronic biometric identification and location ticket at an airport, [12]. UWB positioning is an emerging technology with many potential benefits for security.…”
Section: Planned Work With the Gait Analysis Laboratorymentioning
confidence: 99%